1998
DOI: 10.1002/(sici)1097-0282(199607)39:1<95::aid-bip10>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of the sweet protein brazzein

Abstract: The sweet protein brazzein isolated from the fruit of the African plant, Pentadiplandra brazzeana Baillon is 2000‐500 times sweeter than sucrose, and consists of 54 amino acid residues with four intramolecular disulfide bonds. Brazzein was prepared by the fluoren‐9‐yl‐methoxycarbonyl solid‐phase method, and was identical to natural brazzein by high performance liquid chromatography, mass spectroscopy, peptide mapping, and taste evaluation. The D enantiomer of brazzein was also synthesized, and was shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…38−42 Our ratios of the recognition threshold values for the three brazzein forms and the control substance sucrose were consistent with those of Assadi-Porter et al 2 These authors observed, in line with our results, that the threshold for des-pyrE-bra brazzein produced using E. coli was 2 times lower than that of the natural brazzein, which is ∼80% pyrE-bra and ∼20% des-pyrE-bra. 5 Moreover, the sweetness potencies determined here correspond well with those previously indicated by Izawa et al, 14 ranging from 500 to 2000, and with those determined by Assadi-Porter et al, 2 being approximately 500 for natural brazzein and 1000 for des-pyrE-bra brazzein produced by E. coli relative to a sucrose solution of 20 g/L.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38−42 Our ratios of the recognition threshold values for the three brazzein forms and the control substance sucrose were consistent with those of Assadi-Porter et al 2 These authors observed, in line with our results, that the threshold for des-pyrE-bra brazzein produced using E. coli was 2 times lower than that of the natural brazzein, which is ∼80% pyrE-bra and ∼20% des-pyrE-bra. 5 Moreover, the sweetness potencies determined here correspond well with those previously indicated by Izawa et al, 14 ranging from 500 to 2000, and with those determined by Assadi-Porter et al, 2 being approximately 500 for natural brazzein and 1000 for des-pyrE-bra brazzein produced by E. coli relative to a sucrose solution of 20 g/L.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Brazzein combines a long history of human consumption, high sweet potency (from 500-to 2000-fold sweeter than a sucrose solution on a weight basis and from 9500-to 38 000-fold on a per-molecule basis), high water-solubility, and exceptional thermostability. 2,5,14,15 In addition, brazzein tastes purely sweet with no sourness, saltiness, or bitterness, making it a good alternative to artificial sweeteners. 5 Because of the difficulties in obtaining brazzein from its natural source, brazzein has been expressed using various recombinant expression systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Non-carbohydrate sweet-tasting substances include several chemically distinct groups of small molecule artificial sweeteners, such as sucralose, saccharin, cyclamate, and acesulfame K, as well as dipeptide sweeteners, such as aspartame and neotame. Sweet-tasting proteins have been found as naturally occurring molecules from plants (or rarely from animals) including thaumatin 1, monellin 2, mabinlin 3, brazzein 4; 5, eggwhite lysozyme 6, and curculin/neoculin 7. In addition, a pure sweet-antagonist protein, the glycoprotein RBP from chicken egg, has been reported to inhibit specifically the taste of sweet-protein but not carbohydrates or artificial sweeteners 8…”
Section: Introductionmentioning
confidence: 99%
“…The major form, with a pyroglutamic acid (pGlu) at its Nterminus, consisting of 54 amino acid residues, is 500-2000 times sweeter than sucrose. Nevertheless, the minor form (despGlu1), without the N-terminal pGlu, and thus bearing only 53 amino acid residues, is twice as sweet as the major form (Izawa et al, 1996).…”
Section: Introductionmentioning
confidence: 99%